Surface pasteurization. Estimating surface processing temperature and thermal load in surimi through heat transfer modelling and reflectance spectroscopy - Skara, T; Stormo, S.K; Skipnes, D; Kondjoyan, Alain; Sivertsen, A; Van Derlinden, E.; Valdramidis, V; Van Impe, J. (HAL CCSD, 2013)
International audience